PENGARUH PENGETAHUAN PAJAK DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SANKSI PAJAK SEBAGAI VARIABEL MODERASI - Anggarwati, Firda; Umaimah, Umaimah (LPPM STIE Muhammadiah Bandung, 2025)
Tax compliance with sanctions as a moderation variable is the focus of this study, which also seeks to understand the role of taxpayer socialization and tax expertise. The main data of this study came from questionnaires and were based on a quantitative descriptive approach. The sampling method is based on lemeshow. We use Google Forms to distribute surveys by using broadcast chat to collect data. There are 96 surveys that have been processed. Structural equation modeling analysis is used to examine the data. According to the conclusions of this study, tax socialization significantly affects taxpayer compliance, although tax penalties cannot reduce the effects of tax socialization and tax knowledge. On the other hand, tax knowledge has little influence on taxpayer compliance.